Voltage vulnerability curves: Data-driven dynamic security assessment of voltage stability and system strength in modern power systems - Aleksandar Boričić; Marjan Popov (International Journal of Electrical Power & Energy Systems)
Power systems evolve towards more renewable and less conventional electricity supply. This, however, brings significant technical challenges, as conventional sources naturally provide system resilience. One of the key dimensions of this resilience is system strength, which is rapidly depleted with the phase-out of fossil-based synchronous generation. This paper commences by exploring the intricate steady- and dynamic-state aspects of system strength, and consequently elevated risks of voltage instability. A new holistic definition of system strength is further proposed. Considering the stability challenges of modern power systems, grid operators need to be aware of any vulnerable grid sections and dangerous operating scenarios to always ensure system security and stability. Nevertheless, the rising complexity of modelling and analysis of dynamics in modern power systems makes this task increasingly challenging. The large number of grid locations with complex inverter-based generation and load, paired with parameter uncertainty, make deterministic analytical analyses of voltage stability and system strength increasingly challenging and time-consuming. A novel data-driven voltage stability and system strength assessment method, termed Voltage Vulnerability Curves (VVCs), is hereby proposed to address these challenges. The method is designed to cut through the complexity of modern power systems’ dynamics and provide advanced system strength and voltage vulnerability insights.